Dynamic performance of a point absorber WEC considering nonlinear hardening spring under irregular waves - Zongyu Chang; Zhenhua Hou; Zhongqiang Zheng (International Marine Energy Journal, 2023)
Wave energy is a kind of clean renewable energy that is huge and still need further research. Point absorber wave energy converter (PA-WEC) is widely utilized for offshore power devices. The PA-WEC utilizes the heave motion to drive linear electric generator or a hydraulic motor to generator using power take off (PTO) system. And the PTO system usually is assumed to be a linear spring and a linear damper. Because of the larger motion, the PTO system, which exhibited non-linear behavior, is considered as linear spring with the nonlinear hardening spring and a linear damper. Through the time domain method, the dynamic model of the PA-WEC is developed under irregular waves. The state space model replaced the convolution term in the frequency domain equation. The dynamic response of the PA-WEC is researched considering different environmental parameters by Runge-Kutta method. Then the power and power ratio performance of the system is obtained. Compare with the linear WEC, the results show that the nonlinear WEC can increase the power captured in irregular waves.